Exposure to Solar UV During Outdoor Construction Work in Britain. Issue 2 (10th March 2020) - Cherrie, John W; Nioi, Amanda; Wendelboe-Nelson, Charlotte; Cowan, Sue; Cherrie, Mark; Rashid, Shahzad; Cowie, Hilary; Ritchie, Peter; Lansdown, Terry C
Abstract: Excessive exposure to ultraviolet (UV) radiation from the sun in summer can cause skin cancer and in Britain there are around 1500 new cases of non-melanoma skin cancer (NMSC) each year, caused by exposure to solar UV at work. Little is known about the magnitude of UV exposure amongst outdoor construction workers in Britain, although this is one of the main groups at risk. The aim of this paper is to summarise measurements of erythema-weighted UVB radiation amongst construction workers in Scotland and the Southeast of England and interpret the data in terms of the risk of NMSC. The measurements were made as part of an intervention study using short mobile phone text messages to alter worker behaviour to either reduce UV exposure in summer or increase serum vitamin D in winter; the intervention is only briefly reported here. Data were collected from 67 workers from 9 worksites, of whom 41 provided measures of UV exposure for 758 working days. Daily exposure ranged from 0 to 13.47 standard erythema dose (SED), with the mean exposure for outdoor workers being 2.0 SED and the corresponding value for indoor workers being 0.7 SED. These data were obtained from a sensor located on the back of the workers hard hat; others have measured exposure on the wrist or upper arm and these locations probably, on average, have higher levels of UV exposure. It is likely that an outdoor construction worker in Britain could accumulate sufficient solar UV exposure over 30–40 years of work to more than double their risk of NMSC. We argue that employers in Britain should take a more proactive approach to manage sun safety and they should take responsibility for skin health surveillance for their workers.